Integration of digital learning media to improve literacy skill students state elementary school 02 Tugu Harum - Najib, Khasbi Ainun; Pertiwi, Ratih Purnama; Kuernianti, Devi (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to improve students’ Indonesian language literacy skills through the integration of digital learning media at SD Negeri 02 Tugu Harum. The research used a classroom action research (CAR) design involving 49 students and was conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The digital learning media used included interactive applications, educational videos, and online learning platforms to support reading, writing, and speaking activities. Data were collected through literacy tests administered before the action and at the end of each cycle, as well as learning motivation questionnaires. The data were analyzed descriptively by comparing students’ literacy scores across the initial condition, Cycle I, and Cycle II. The results showed a consistent improvement in students’ Indonesian language literacy skills, with average increases of 19.5% in reading, 21.1% in writing, and 20.3% in speaking skills. Students’ learning motivation also improved, as indicated by higher participation and confidence during learning activities. These findings indicate that the integration of digital learning media contributes positively to the improvement of Indonesian language literacy skills and learning motivation among elementary school students.